Update on perioperative management of the child with asthma - Francesco Dones; Grazia Foresta; Vincenzo Russotto (MDPI AG, 2012)
Asthma represents the leading cause of morbidity from a chronic disease among children. Dealing with this disease during the perioperative period of pediatric surgical procedures is, therefore, quite common for the anesthesiologist and other professionalities involved. Preoperative assessment has a key role in detecting children at increased risk of perioperative respiratory complications. For children without an optimal control of symptoms or with a recent respiratory tract infection elective surgery should be postponed, if possible, after the optimization of therapy. According to clinical setting, loco-regional anesthesia represents the desirable option since it allows to avoid airway instrumentation. Airway management goals are preventing the increase of airflow resistance during general anesthesia along with avoiding triggers of bronchospasm. When their use is possible, face mask ventilation and laringeal mask are considered more reliable than tracheal intubation for children with asthma. Sevoflurane is the most commonly used anesthetic for induction and manteinance. Salbutamol seems to be useful in preventing airflow resistance rise after endotracheal intubation. Mechanical ventilation should be tailored according to pathophysiology of asthma: an adequate expiratory time should be setted in order to avoid a positive end-expiratory pressure due to expiratory airflow obstruction. Pain should be prevented and promptly controlled with a loco-regional anesthesia technique when it is possible. Potential allergic reactions to drugs or latex should always be considered during the whole perioperative period. Creating a serene atmosphere should be adopted as an important component of interventions in order to guarantee the best care to the asthmatic child.